Efektifitas Metode Participatory Learning terhadap Peningkatan Literasi Kesehatan pada Masa Pandemi COVID-19 - Cahyanti, Erin Tri; Lubis, Syafana Marasati; Hidayah, Siti Nur Rofiatul; Andhika, Hafidh Putra; Arifah, Izzatul (UI Scholars Hub, 2023)
Background. The COVID-19 pandemic has given rise to a new issue, known as the infodemic about COVID-19. Individual behaviors in preventing the transmission of COVID-19 are influenced by their level of health literacy. While students are expected to have good health literacy, data shows that a high proportion of students have a lower level of health literacy. Aim. The research aims to assess the effectiveness of participatory learning methods based on a website in improving health literacy among students during the COVID-19 pandemic. Method. The research design is an experimental design, specifically a pretest-posttest control group with randomization design. The research sample was randomly selected from 6 universities in Solo Raya that had completed the eHEALS health literacy screening questionnaire. Each intervention and control group had 41 respondents, and data analysis was performed using T-Test Result. The intervention of participatory learning methods based on a website significantly improved students' health literacy during the COVID-19 pandemic (p=0.031). Similar educational efforts targeting a broader audience are needed to enhance health literacy and promote the implementation of health protocols during the COVID-19 pandemic